Antimicrobial Use-Related Problems and Predictors among Hospitalized Medical In-Patients in Southwest Ethiopia: Prospective Observational Study - Yadesa, Tadele Mekuriya; Gudina, Esayas Kebede; Angamo, Mulugeta Tarekegn (PloS one, 2015)
The spread of antimicrobial resistance in developing countries is associated with complex and interconnected factors, such as excessive and unnecessary prescribing of antimicrobials, increased self-prescribing by the people and poor quality of available antimicrobials. Moreover, the failure to implement infection control practices and the dearth of routine susceptibility testing and surveillance magnify the problems. This may spread the inappropriateness of prescribing, ending up with the spread of antimicrobial resistance. The aim of this study was to assess antimicrobial use related problems and associated factors among patients admitted at Jimma University specialized hospital. A hospital based prospective observational study design was employed at medical wards of Jimma University specialized hospital, Ethiopia. Data collected from patient medication charts and from the patients was analyzed using SPSS, version 16.0. Logistic regression was used to determine the associations between variables. Statistical significance was considered at p-value <0.05. Out of 152 study participants, at least one antimicrobial use problem was identified among 115(75.7%). Accordingly, additional antimicrobials were needed by 45(29.6%) of the patients, whereas they were unnecessary among 44(28.9%). Similarly, 17% of the patients were noncompliant to at least one antimicrobial therapy, while 8.6% experienced at least one type of adverse drug reaction. On the other hand, the coverage of the infectious medical condition in the national guidelines (AOR = 4.888) and the duration of hospital stay (AOR = 3.086) were the determinants of the antimicrobial use problems. Most of the antimicrobial use problems identified were related to delay of initiation of effective antimicrobials and excessive use; use without indication or using duplicates of broad spectrum antimicrobials or use for longer duration than recommended. The coverage of the infectious medical condition in the national treatment guidelines and the duration of hospital stay were the determinants of the antimicrobial use problems.